(untitled) (Medico Legal Update, 2020)
An optimal diet before and during pregnancy cannot guarantee a successful outcome of pregnancy; it can improve the chance of a healthy newborn baby, a healthy mom, and a healthy future for both. A woman who is well nourished and within her healthy weight range prior to conception provides an environment conducive to normal fetal growth and development during the critical first trimester of pregnancy. Study design and population. This study used data from the mothers and child care unit in health centers, a prospective cohort study in central Al.Hillah designed to investigate the maternal dietary patterns during the second trimester and risk factors for preterm birth. second trimester of pregnant women were recruited at 24–29 wk of gestation from prenatal clinics at the MCH Services Department. Stratified and randomly selected out-patient clinics between Jan 2016 and April 2017. All participants gave written informed consent at the time of recruitment. Data were collected via interviews and self-administered questionnaires, including an MNA to collect dietary information. Socio-demographic information and health behaviors were collected via interviews. during the first 6 mo of pregnancy was collected from self administered questionnaires. pregnancy BMI was based on height measured at the first prenatal clinic visit and self-reported pregnancy weight. Missing pregnancy weight was imputed on the basis of the first prenatal care visit (19). Total of (50) pregnant women were enrolled into the PIN study. Only pregnancies with complete dietary information were included in this study (n = 50). Data analyses the related data by using SPSS 23.0 software program. A level of P < 0.05 was considered statistically signifificant. Characteristics of the intervention group and comparison group were compared using t-tests for continuous variables and ?2-tests for categorical variables. Most of the sample (44.9%) had (21-26) years aged,(36.7%) with (56-66 kg ) body weight and (42.9% ) had 140-150 cm ) body height